Adsorption of basic dye onto raw and surface‐modified agricultural waste. Issue 1 (26th February 2013) - Senthil Kumar, P.; Palaniyappan, M.; Priyadharshini, M.; Vignesh, A.M.; Thanjiappan, A.; Sebastina Anne Fernando, P.; Tanvir Ahmed, R.; Srinath, R.
<x xml:space="preserve">Abstract</x> The application of raw Bangalora (Totapuri) mango seed kernel powder (RMS) and surface‐modified Bangalora (Totapuri) mango seed kernel powder (SMMS) for the removal of methylene blue (MB) dye from aqueous solution was investigated under ambient conditions. The adsorbent was characterized by the FTIR and SEM analyses. Batch adsorption studies were conducted by varying the solution pH, adsorbent dose, initial MB dye concentration, and contact time. The optimum conditions for the adsorption of MB dye onto the adsorbent was found to be: pH (8.0), adsorbent dose (1.0 g: RMS and 0.4 g: SMMS), contact time (60 min: RMS and 30 min: SMMS), temperature of 30°C for an initial MB dye concentration of 100 mg/L. Adsorption isotherm data were analyzed by the Langmuir, Freundlich, Temkin, and Dubinin‐Radushkevich isotherm models. Experimental data was successfully applied to the Freundlich model than the Langmuir model, and the maximum monolayer adsorption capacity was found to be greater for SMMS than the RMS. Adsorption kinetics was tested with the pseudo‐first‐order and pseudo‐second‐order kinetic models. The kinetic results show that the adsorption process followed the pseudo‐second‐order kinetic model. Adsorption kinetic data were further applied to the intraparticle diffusion, Boyd kinetic and shrinking core models to explain the adsorption mechanism. Adsorption mechanism results shows that the adsorption process was controlled by both internal and external diffusion. The results of this study show that the SMMS could be used as an effective and low‐cost adsorbent for the removal of dyes from aqueous solution. © 2013 American Institute of Chemical Engineers Environ Prog, 33: 87–98, 2014